Effects of defect dipoles on the colossal permittivity of ambipolar co-doped rutile TiO2 ceramics. (August 2020) - Oliveira de Lira, Stefane; de Sousa e Silva, Raphael Lucas; Banerjee, P.; Franco, A.
Abstract: This study investigated the colossal permittivity of ambipolar co-doped rutile TiO 2 ceramics obtained using the solid state sintering method for use as alternatives to high-performance dielectric materials. Ambipolar co-doping was conducted with compositions comprising Ti 0.995 ( Nb 1.33 ( Al 1 − x Cr x ) 0.666 ) 0.005 O 2, where x = 0, 0.3, 0.5, 0.7, 0.9, and 1. Analysis based on X-ray diffraction, Fourier transform-infrared spectroscopy, and Raman spectra showed that the dopants did not alter the crystal structure of rutile but they created some distortion in the TiO 2 lattice. Analysis of the dielectric properties showed that the ceramics exhibited relatively low loss with colossal permittivity at room temperature. The existence of an asymmetrical relaxation mechanism was demonstrated with the Fuoss–Kirkwood dielectric model. The combined functions of defect dipoles and localized electrons were investigated for ambipolar co-doped TiO 2 ceramics for use in high-density RAM and microelectronics applications. Highlights: New ambipolar TiO2 ceramics with colossal permittivity and low loss. Ambipolar co-doping obtains localized electrons with highly correlated structure. Localized electrons form defect dipoles in TiO2 ceramics. Defect dipoles generate colossal permittivity and low loss. Low loss and colossal permittivity suitable in materials for use in capacitors.